Automatic Cell Planning Method for Radio Network Optimization - Putri, Hasanah; Ahmad, Izanoordina; Hikmaturokhman, Alfin; Haura Putri, Dwi (Society of Visual Informatics, 2024)
As the first step in building a wireless communication network, wireless network optimization is crucial since it determines how the network will be built scientifically. Numerous challenges remain in the way of the Radio Network's deployment in Indonesia, not the least of which is the still-uneven coverage region. The Kiaracondong region in Bandung is one of the numerous areas in Indonesia that are still considered to be